Health-promoting properties of fruit and vegetables [ - Terry, Leon A. [ (Leon Alexander)] (Wallingford, Oxfordshire, UK : CABI, 2011)
Fruits and vegetables are among the richest sources of ascorbic acid, other antioxidants and they produce specific bioactive compounds. A general consensus from health experts has confirmed that an increased dietary intake of antioxidant compounds foundin most fresh produce types may protect against oxidative damage caused by free radicals and reduce the incidence of certain cancers and chronic diseases. This work collectively discusses and reviews empirical data on the health promoting properties of all fresh produce types, and it provides detailed information on the identity, nature, bioava.
Includes bibliographical references and index
Keywords: Fruit in human nutrition; Vegetables in human nutrition